A Digital Supply Chain Model for Tourism Management in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
The paper were to study and to evaluate a digital supply chain model for tourism management in Thailand. The samples in the paper study consisted of ten purposively selected experts consisted of ten experts on supply chain management, five experts on Digital Technology, Data were analysed by arithmetic mean and standard deviation. The research findings model eight elements namely main components, Suppliers, Tours Operator, Agents , Customers, Satisfaction and Feedback. The ten experts agree that a digital supply chain model for tourism management in Thailand was high suitability that mean a digital supply chain model for tourism management in Thailand to may be applied in support the tasks.